2008
DOI: 10.1029/2008gl034014
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap between seismically and geodetically detected slow earthquakes

Abstract: Recently observed unusual seismic events: deep low frequency earthquakes and tremor, very low frequency earthquakes, and slow slip events form a family of slow earthquakes that are governed by a scaling law different from ordinary earthquakes. Guided by this scaling law, we have observed previously unknown events, with source duration of 20–200 s and moment magnitude of 3–4, under the Kii Peninsula in western Japan. These events radiate seismic energy in the 2–8 Hz band in direct proportion to their seismic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
194
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 117 publications
(215 citation statements)
references
References 20 publications
18
194
3
Order By: Relevance
“…The Cascadia SSEs, a slow earthquake sequence , and short-term SSEs (Sekine et al, 2010) all fall within the LogM 0 ∼ LogT trend. As pointed out by Ide et al (2008), the lower slope characteristic of data from a particular study or geographic region may represent an artifact, potentially reflecting the saturation of a fault parameter from limited observations or the methodology. preceded by longer intervals.…”
Section: Seismic Moment Versus Fault Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The Cascadia SSEs, a slow earthquake sequence , and short-term SSEs (Sekine et al, 2010) all fall within the LogM 0 ∼ LogT trend. As pointed out by Ide et al (2008), the lower slope characteristic of data from a particular study or geographic region may represent an artifact, potentially reflecting the saturation of a fault parameter from limited observations or the methodology. preceded by longer intervals.…”
Section: Seismic Moment Versus Fault Areamentioning
confidence: 99%
“…Here we reassess this logarithmic scaling relationship by adding data of more recent SSEs (Fig. 3), including two slow earthquake sequences in Japan (data from Ide et al, 2008 andSekine et al, 2010). Note that there is a lack of observations in our dataset for seismic moment within ∼1:0e15 1:0e17 N·m corresponding to duration ranging from minutes to days.…”
Section: Seismic Moment Versus Fault Areamentioning
confidence: 99%
“…Slow slip events (SSEs) at various scales have been observed and studied in many regions worldwide over the past two decades (e.g., Linde et al 1996;Dragert et al 2001;Obara 2002;Kostoglodov et al 2003;Ide et al 2007aIde et al , 2008Ide 2012). It is considered that SSEs occur along the same interface as ordinary tectonic earthquakes (Ide et al 2007b), generally at the deeper extent of the shallow locked region, below the brittle-ductile transition.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the group of LFEs is different to the group of ordinary earthquakes and that the scaled energy (i.e., the ratio of seismic energy to seismic moment) of the LFEs is much smaller than that of ordinary earthquakes. In the Kii Peninsula of southwest Japan, the envelope of tremors with high frequency (2-8 Hz) is proportional to that of low frequency (0.005-0.500 Hz) and the moment rate function, and the scaled energy is of the order of four to five times smaller than ordinary earthquakes (Ide et al 2008). The envelope of the LFEs is also similar to the VLFEs at IGK (Fig.…”
Section: Maximum Amplitudes Of Lfe-vlfes and Ordinary Earthquakesmentioning
confidence: 53%
“…2c-e). Calculating the seismic energy using the equation for the RMS waveform of LFEs (Ide et al 2008), and calculating the seismic moment using the empirical equation for the maximum amplitude and moment magnitude (Ando et al 2012), suggested that the scaled energy was of the order of 10 −11 for the three events shown in Fig. 2c-e.…”
Section: Maximum Amplitudes Of Lfe-vlfes and Ordinary Earthquakesmentioning
confidence: 99%